Guard cells: a dynamic signaling model - Fan, L.M.; Zhao, Z.; Assmann, S.M.
The year 2003 has provided a continuing accretion of knowledge concerning the diverse ways in which guard cells sense and respond to abscisic acid. A deeper understanding of the biochemical mechanisms governing the response of guard cells to blue light has been gained, and new insights have been garnered regarding roles of the extracellular matrix in stomatal regulation.